URGENSI PENGUATAN PERAN KOMISI YUDISIAL DALAM MELAKUKAN PENGAWASAN HAKIM DI INDONESIA - Jasmi, Muhammad; Suasono, Edy (Faculty of Law, Universitas Tanjungpura, 2023)
AbstractThe Judicial Commission was born in the reform era when the third amendment to the 1945 Constitution of the Republic of Indonesia in 2001 coincided with the Regional Representative Council and the Constitutional Court, although the Judicial Commission is a new institution, its existence has very strong legal justification because it is strictly regulated in the Law. The 1945 Constitution of the Republic of Indonesia and its authority are granted by the constitution, so that it has a very strong position. However, the authority of the Judicial Commission tends to be incomplete because it still requires further action from other institutions. For example, in the selection of candidates for Supreme Court justices, the Judicial Commission has the duty and authority to propose candidates for Supreme Court justices. However, in the end the Judicial Commission's proposal was still rejected by the People's Representative Council (DPR). In practice, the House of Representatives (DPR) once disapproved of names proposed from the selection results of the Judicial Commission, even though a number of prominent community figures were involved in the selection process.Based on the above, the research method in this study is normative legal research. Normative legal research is legal research conducted by examining literature or secondary data. In addition to using library materials, this research also uses a statutory approach. The statutory approach (statute approach) is usually used to examine statutory regulations which in their norms still lack or even foster deviant practices both at the technical level and in practice in the field.The conclusion obtained in this study is that the Judicial Commission is a state institution mandated by the 1945 Constitution which has the authority to maintain and uphold the dignity, honor, nobility and also the behavior of judges. The Judicial Commission as a State institution whose duties are related to judicial power which is